Probing prompting strategy to improve young learner’s speaking skills in Palopo city - Iksan, Muhammad; Yahya, Amalia; Rosmita, Rosmita (Englisia Journal, 2021)
This paper attempted to examine the efficacy of the Probing-Prompting Technique in teaching speaking skills to young beginner English learners. This study employed the experimental method with a pre-experimental design. The subjects of this study were English learners age 16 to 19 in Palopo City who were chosen using a purposive sampling technique to select the active learners. Using the oral presentation task, the writers compiled three aspects of the learner's score, i.e. accuracy, fluency, and comprehensibility. The experimental teaching was conducted in six meetings, preceded by a pre-test and ended by a post-test. The pre-test found that the learners’ speaking skill ability is low (mean score: 25.75). In post-test, the authors found that the learners’ language ability substantially improved. Some learners get significant improvement in every aspect of speaking skills, i.e. fluency, accuracy, and comprehensibility. The strategy also contributed to the increase in the mean score (51.50). As a result, the writers concluded that Probing-Prompting Strategy successfully improves the learners’ speaking skills. It is proven by the result of the paired-sample test which showed that t-count (7,584) is higher than t-table (2,365).